Balintawak Market Village integrated market and housing development - Del Rosario, Julia Nicole G.; Madrid, Dolores Cecelia T. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Due to Balintawak’s high accessibility and connectivity, it was identified by Quezon City as one of its five Growth Districts to distribute growth in the city. It bears the title of “Gateway from the North”, and is known for its success as a trading center for agricultural produce from northern Luzon provinces.
New road developments continue to increase the district’s connectivity to different parts of Luzon. This is assumed to bring in more pedestrian and vehicular traffic, thus raising the call for other forms of income generating and commercial activities apart from agricultural ones. Balintawak’s urban fabric is set to change as the district continues to grow and develop. The Balintawak-Cloverleaf Market is one of the developments affected by this change. The pattern of supermarkets replacing palengkes or wet markets is becoming prevalent in the Philippines. In fact, Ayala has already offered to buy the property to expand its mixed-use development located behind the market.
The proposed redevelopment of the Balintawak-Cloverleaf market reinvents the palengke building typology by adding new functions -- specifically housing and retail spaces -- to adapt it to changing consumer needs and reinforce its importance as part of a developing district’s urban landscape.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Balintawak Cloverleaf Market; Housing; Markets